2011
DOI: 10.1136/ard.2010.134445
|View full text |Cite
|
Sign up to set email alerts
|

Should imaging be a component of rheumatoid arthritis remission criteria? A comparison between traditional and modified composite remission scores and imaging assessments

Abstract: Using more stringent remission criteria resulted in reduced signs and symptoms of inflammation, but the percentage of joints with PD activity was not reduced, even in those without signs or symptoms. These data suggest that clinical criteria are sufficiently insensitive to detect low but clinically relevant levels of inflammation accurately.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

11
116
1
6

Year Published

2012
2012
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 196 publications
(134 citation statements)
references
References 19 publications
11
116
1
6
Order By: Relevance
“…These observations are also supported by a recent article by Balsa et al, who demonstrated that remission as classified by the SDAI is closer to the concept of an absence of inflammatory activity, when the absence of a positive PD signal is considered as a gold standard (41). In addition, the study by Saleem et al (42) showed that a larger percentage of patients in SDAI remission were in "imaging remission," as defined by the absence of GS synovitis and PD signal as compared to patients in DAS28 remission.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…These observations are also supported by a recent article by Balsa et al, who demonstrated that remission as classified by the SDAI is closer to the concept of an absence of inflammatory activity, when the absence of a positive PD signal is considered as a gold standard (41). In addition, the study by Saleem et al (42) showed that a larger percentage of patients in SDAI remission were in "imaging remission," as defined by the absence of GS synovitis and PD signal as compared to patients in DAS28 remission.…”
Section: Discussionsupporting
confidence: 77%
“…The improved sensitivity of novel imaging techniques has led to the notion of incorporating imaging into remission criteria for RA (42). As suggested by our study, incorporating imaging into measures of disease activity may improve the reliability of such systems and have marked effects on the classification of patients.…”
Section: Discussionmentioning
confidence: 93%
“…One way of addressing this concern is by using imaging technology such as ultrasound (US) or magnetic resonance imaging. Previous studies have demonstrated that ongoing synovitis can be detected by US in up to 62% of patients in clinical remission (19)(20)(21) and that synovitis demonstrated by power Doppler ultrasound (PDUS) correlates with both progression of structural damage (22) and risk of subsequent RA flare (23). As a result, the use of US assessment for patients in clinical remission has been proposed (24).…”
Section: Introductionmentioning
confidence: 99%
“…Sonography has a high sensitivity to detect joint inflammation and RA-specific bone lesions, as well as a high specificity to exclude synovitis in patients with noninflammatory joint pain (4). In patients with established RA, it was demonstrated that up to 50% of patients still have active synovitis at ultrasound examination despite clinical remission (5) and, conversely, sonography excluded active inflammation in up to 20% of cases with painful joint swelling (6).…”
Section: Introductionmentioning
confidence: 99%